An update of “Cost-effectiveness of rotavirus vaccination in the Netherlands: the results of a Consensus Rotavirus Vaccine model” - Tu, Hong Anh T (BioMed Central, 2013)
BACKGROUND: To update a cost-effectiveness analysis of rotavirus vaccination in the Netherlands previously published in 2011. METHODS: The rotavirus burden of disease and the indirect protection of older children and young adults (herd protection) were updated. RESULTS: When updated data was used, routine infant rotavirus vaccination in the Netherlands would potentially become an even more cost-effective strategy than previously estimated with the incremental cost per QALY at only €3,000-4,000. Break-even total vaccination costs were indicated at €92–122, depending on the applied threshold. CONCLUSIONS: We concluded that the results on potentially favourable cost-effectiveness in the previous study remained valid, however, the new data suggested that previous results might represent an underestimation of the economic attractiveness of rotavirus vaccination.